BIOMETRIC ASPECTS OF FRUIT AND SEEDS Poincianella pluviosa var. peltophoroides (Benth.) L.P. Queiroz - Ferreira, Vinícius Staynne Gomes; Souto, Patrícia Carneiro; Borges, César Henrique Alves; Freitas, Amanda Lira; Novais, Danilo Brito; Pinto, Marilia Gabriela Caldas (Biofix Scientific Journal, 2020)
Species arboreal, native of the Atlantic Forest biome, Poincianella pluviosa var. peltophoroides (Benth.) L.P. Queiroz is widely used in urban landscaping due to the beauty of its flowering and indicated for the recovery of degraded areas as an initial or pioneer secondary species. The objective of the study was to characterize the fruits and seeds biometrically, thus helping in its conservation and improvement. The work was conducted at the Federal University of Campina Grande, campus of Patos-PB, and the fruits were collected manually in matrices located on campus, using as a selection criterion those who were mature. To obtain the biometric data, the fruits were selected and separated 100 fruits and 100 seeds at random. To measure the biometric variables (length, width and thickness) of the fruits and seeds, a digital caliper with a precision of 0.1 mm was used and then the amplitude of the classes of each analyzed variable was calculated. The results showed that the fruits presented variation in the length of 4.51 to 10.53 cm, however, the predominance of fruit frequency was in the class of 6.03-6.77 cm. The seed length varied from 0.918 to 1.208 cm, with a higher incidence in the class of 1.064-1.112 cm, where it concentrated about 45% of the seeds. It is concluded that the fruits Poincianella pluviosa var. peltophoroides presented greater uniformity in the variable length and their seeds presented greater uniformity in the biometric variables in which they were evaluated, being this a favorable criterion for its propagation.